2012
DOI: 10.1016/j.pscychresns.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Impaired inhibitory control in ‘internet addiction disorder’: A functional magnetic resonance imaging study

Abstract: ‘Internet addiction disorder’ (IAD) is rapidly becoming a prevalent mental health concern in many countries around the world. The neurobiological underpinning of internet addiction should be studied to unravel the potential heterogeneity. The present study examines the neural correlates of response inhibition in males with and without IAD using an event-related functional magnetic resonance imaging (fMRI) Stroop task. The IAD group demonstrated greater ‘Stroop effect’-related activity in the anterior and poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
2
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(148 citation statements)
references
References 52 publications
10
125
2
11
Order By: Relevance
“…These findings have now been replicated using fMRI, 98 showing that when using a go/no-go paradigm, individuals diagnosed with IA are not able to inhibit their responses relative to healthy controls, and this has been linked to the lack of engaging the former's indirect frontal-basal ganglia pathway. A similar study using the Stroop paradigm with Internet addicts in comparison with healthy controls has furthermore shown that Internet addicts had stronger "Stroop effect"-related activity in the anterior and posterior cingulate cortices, 99 supporting the contention that Internet addicts have impaired inhibitory control. A comparable Stroop paradigm study furthermore indicated Internet addicts use more cognitive resources for executive control and attention relative to healthy controls, as identified using fMRI, 100 suggesting their cognitive flexibility is impaired.…”
mentioning
confidence: 69%
“…These findings have now been replicated using fMRI, 98 showing that when using a go/no-go paradigm, individuals diagnosed with IA are not able to inhibit their responses relative to healthy controls, and this has been linked to the lack of engaging the former's indirect frontal-basal ganglia pathway. A similar study using the Stroop paradigm with Internet addicts in comparison with healthy controls has furthermore shown that Internet addicts had stronger "Stroop effect"-related activity in the anterior and posterior cingulate cortices, 99 supporting the contention that Internet addicts have impaired inhibitory control. A comparable Stroop paradigm study furthermore indicated Internet addicts use more cognitive resources for executive control and attention relative to healthy controls, as identified using fMRI, 100 suggesting their cognitive flexibility is impaired.…”
mentioning
confidence: 69%
“…Such a proposal was based on the extensive literature supporting that impulsivity is a hallmark of addictive behaviors [26,27], including behavioral addictions such as disordered gambling [28,29] and Internet addiction [30,31]. Unfortunately, in the framework of PMPU, available evidence, although promising, has relied on either self-reports or clinical case studies.…”
Section: Problematic Mobile Phone Use As a Behavioral Addictionmentioning
confidence: 99%
“…This is mainly due to the fact that the areas of the video game addict's brain that respond to stimuli are similar from those of substance dependence's 19 and Internet addicts 20,21 .…”
Section: Psychiatric Characteristicsmentioning
confidence: 99%